2004
DOI: 10.1002/anie.200461215
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of CO with N2O on Gas‐Phase Platinum Clusters

Abstract: The complete catalytic cycle of CO oxidation with N2O is shown to occur on Ptn+ (see scheme); for Pt7+ it involves six different elementary reactions. Poisoning of the catalyst by sequential addition of CO is observed. The extent of poisoning can be adjusted with the ratio of N2O and CO partial pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 48 publications
2
85
0
2
Order By: Relevance
“…Furthermore, cationic Pt x + (x = 6-8) [6] as well as anionic clusters Pt x À (x = 3-6) [4g,h, 7] permit efficient catalytic cycles. The energetic requirement for this kind of O-atom transport is defined by the O-atom affinities (OAs) of the three species given in Equations (2) and (3), that must fulfill the requirement given in Equation (4).…”
Section: /Ptomentioning
confidence: 99%
“…Furthermore, cationic Pt x + (x = 6-8) [6] as well as anionic clusters Pt x À (x = 3-6) [4g,h, 7] permit efficient catalytic cycles. The energetic requirement for this kind of O-atom transport is defined by the O-atom affinities (OAs) of the three species given in Equations (2) and (3), that must fulfill the requirement given in Equation (4).…”
Section: /Ptomentioning
confidence: 99%
“…Nothing is known so far concerning the reactions of gas-phase gold and silver clusters, although N 2 O was employed to oxidize other transition metal clusters. 7 In a very recent communication, Hamilton et al reported evidence of infrared driven surface chemistry of N 2 O on Rh + n clusters. 8 The adsorption of CO on pure gold [9][10][11][12] and silver [10][11][12] cluster cations and anions was investigated previously, revealing size specific CO saturations and the strongest binding energies of CO to positively charged gold clusters.…”
mentioning
confidence: 99%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) is a well suited tool to investigate bimolecular cluster ion-molecule reactions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In order to determine absolute rate constants one should know the absolute pressure in the ICR-cell accurately, because the pressure is the main uncertainty.…”
Section: Introductionmentioning
confidence: 99%